A study of developing a spatial entity greenway in the case of Irbid City – Jordan - Bzour, Ansam; Valánszki, István (Landscape Architecture and Art, 2021)
Greenways are urban elements that are designed to show the linear consistency and connectivity between open green spaces and cause a development in the urban texture. As a city starts to grow, the absolute metropolitan development should be followed by an ongoing protection of the rural and urban territories. The nexus between the city development and the fortification of the open agricultural and rural lands is deemed a good strategy in order to result in a homogenous urban fabric of the city. The study aims to present a greenway model of development to work as a prototype applied on an existing route in Irbid City-Jordan by using the methods of testing and analyzing the route during the site visit and by using GIS base maps in order to come up with an absolute combination between monitoring the city growth, maintaining the quality of the agricultural lands and serving the public and local needs in order to result in a more balanced and controlled growth of the city. Irbid city is located in the northern part of Jordan with a radial urban expansion model of growth extending from the historical center and spreading toward the outskirts of the city. Regarding the significant increase in the number of population in Irbid City-Jordan since the 1970s until nowadays and the continuous need for habitats, there was a huge number of housing projects in the inner part of the city that expanded toward the outer part including the rural areas, resulting in a huge lack of agricultural lands and open recreational spaces where people can benefit from. Those spaces form an outlet of the city connected with the inner part by a route. Establishing a greenway along the route raises the integration between people and their lands and encourages farmers to develop and harvest. According to this study, the greenway development, which forms a breath out to the highly built-up area in the city, has become a great tool to result in tremendous beneficial outcomes to the city development.